Impact of biomethane gas on energy and emission characteristics of a spark ignition engine fuelled with a stoichiometric mixture at various ignition advance angles. (15th December 2015) - Sendzikiene, Egle; Rimkus, Alfredas; Melaika, Mindaugas; Makareviciene, Violeta; Pukalskas, Saugirdas
Highlights: Biogas is an environmentally friendly fuel for Otto engines. The impact of supplying additional biomethane gas to a spark ignition engine is evaluated. Engine and environmental characteristics were studied. Using biogas requires operational modifications. Abstract: The impact of supplying additional biomethane gas with composition of 65% methane (CH4 ) and 35% carbon dioxide (CO2 ) to a spark ignition engine on energy and emission characteristics was studied. The tests were performed on a Nissan Qashqai HR 16DE engine, with the engine throttle 15% open, a constant stoichiometric fuel mixture and various ignition advance angles. It was found that an increase in added biomethane gas results the drop in engine power output. This effect had two primary causes. First, the cylinders were refilled less effectively. Second, biogas, by impacting the efficiency and speed of the combustion process, reduces the thermal efficiency of the engine. The second effect can be partially improved by accelerating the combustible ignition mixture. It was also observed that CO2 gas, which is in biogas composition, suppress combustion process which increases the content of carbon monoxide (CO) in exhaust gas, but reduces emissions of nitrous oxide (NO x ). Increased carbon dioxide amount in fuel mixture has small influence on CO2 increase in exhaust gas because the methane in biogases reduces C/H ratio of the fuel mixture. Hydrocarbons which are in methane composition has smaller molecular mass, evaporates and combust easier which has influence on reduced concentration of unburnt hydrocarbons (HC).